Factors and Risks Causing Fraud in Various Countries: Comparison Between Sectors and Regions - Delila Pandora Harlacxienty; Kurnia Illa Allodya; Hwihanus Hwihanus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to analyze the factors and risks that cause fraud in various countries with comparisons between sectors and regions. Using Qualitative method: Meta analysis based on five journals related to fraud (Fraud) in various countries. The purpose of using the meta-analysis method, the method is used to integrate data from different studies so that it can provide more accurate results, rather than the results obtained from a single study, and seeks to understand the mechanism, several factors that may affect the occurrence of fraud in various countries and sectors, including the existence of organizational justice, internal control, opportunity, pressure and rationalization. The results show that fraud is a global problem that requires international solutions, and cooperation between countries and internal communication are indispensable in building a system that can fight organized financial fraud globally. This study aims to provide a deterrent effect, minimize fraud losses and improve control systems. The results of this study are expected to contribute to further understanding of the factors that influence the occurrence of fraud in various countries and sectors, and provide recommendations for preventing and overcoming fraud in various regions.